Simple, Selective and Sensitive Spectrophotometric Method for Determination of Trace Amounts of Lead (II), Cademum (II), Cobalt (II) with Organomercury Compounds - Fatima K. Aziz (Journal of Global Pharma Technology, 2020)
A selective and sensitive reagent of 2-[(2-mercurychlorid, 4-methylphenylImino] methyl phenol (K) was synthesized and studied for the spectrophotometric determination of Lead, Cademum, and cobalt, in detail. At a pH value (7), which greatly increased the selectivity; lead, cademume, cobalt, reacted with (K)to form a 1:1, 1:1, and 1:1 complexes, with absorption peaks at 394, 394, 389 nm, respectively. Under the optimal conditions, Beer’s law was obeyed over the ranges (1X10-6, 1X10-5, 1X10 -4, 1x10-3 1X10-2) mg/L respectively. The apparent molar absorptivity and Sandell’s sensitivities were (0.3, 0.1, 0.2) L·mol-1·cm-1 respectively, and0.027, 0.05, 0.013) μg·cm-2respectively the detection limits were found to be be0.052, 0.036, 0.039) mg/L respectively.